2008
DOI: 10.1128/jvi.02082-08
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Hepatitis Virus Liver Pathology Is Dependent on ADP-Ribose-1″-Phosphatase, a Viral Function Conserved in the Alpha-Like Supergroup

Abstract: Viral infection of the liver can lead to severe tissue damage when high levels of viral replication and spread in the organ are coupled with strong induction of inflammatory responses. Here we report an unexpected correlation between the expression of a functional X domain encoded by the hepatotropic mouse hepatitis virus strain A59 (MHV-A59), the high-level production of inflammatory cytokines, and the induction of acute viral hepatitis in mice. X-domain (also called macro domain) proteins possess poly-ADP-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
187
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(199 citation statements)
references
References 39 publications
11
187
0
1
Order By: Relevance
“…Infection of un-injured C57BL/6 female mice with 5 × 10 5 PFU MHV leads to acute hepatitis infection, but all mice survive and recover and this is associated with clearance of virus from the liver to below levels detectable by plaque assay (~200PFU/g tissue) (Eriksson et al, 2008; Navas et al, 2001). In contrast, all mice that received 5 × 10 5 PFU of MHV 1 week following a complete bilateral crush SCI at thoracic level-T3 died by 6 days post-infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…Infection of un-injured C57BL/6 female mice with 5 × 10 5 PFU MHV leads to acute hepatitis infection, but all mice survive and recover and this is associated with clearance of virus from the liver to below levels detectable by plaque assay (~200PFU/g tissue) (Eriksson et al, 2008; Navas et al, 2001). In contrast, all mice that received 5 × 10 5 PFU of MHV 1 week following a complete bilateral crush SCI at thoracic level-T3 died by 6 days post-infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, DC-T cell interaction in the presence of high Ag doses favors the production of IL-6 and hence the suppression of Treg induction (43). Furthermore, IL-6 is one of the strongly induced proinflammatory cytokines in secondary lymphoid organs during acute MHV infection (46). It is therefore possible that Tregs exert their negative regulatory effects preferably under low Ag dose/low inflammation conditions such as late release of self-antigens during cytopathic virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that the X domain (Mac1) is dispensable for RNA replication in the context of a SARS-CoV replicon (Kusov et al, 2015). Recently, evidence accumulated showing that the X domain plays a role in counteracting the host innate immune response (Eriksson et al, 2008;Kuri et al, 2011;Fehr et al, , 2016.…”
Section: Macrodomain I (Mac1 X Domain)mentioning
confidence: 99%